MYSTIC SECRETS IN TURKISTAN: YASSAVIYA, KUBROVIYA AND NAQSHBANDIYA - Khabib Satorov; Kandakharov Anvarjon Khasanovich (Zeta Repository, 2023)
This article is one of the main issues in Sufism. A perfect person is a person who has good words, good deeds, good morals and knowledge. Sufism pirs call a person to be good-natured, honest and pure, to be one with his word and work, to be one with his tongue, to be knowledgeable, cultured, and spiritual. The concept of Sufism, its essence, directions of the sect have been studied. Also, the Naqshbandi sect and its specific aspects are revealed. In addition, the article compares the importance of the concept of "Perfection" in Sufism . Thoughts and comments aimed at raising the morale of young people were held.